Model reference adaptive system speed estimator based on type-1 and type-2 fuzzy logic sensorless control of electrical vehicle with electrical differential - Khemis, Abderrahmane; Boutabba, Tarek; Drid, Said (Національний технічний університет "Харківський політехнічний інститут", 2023)
In this paper, a new approach for estimating the speed of in-wheel electric vehicles with two independent rear drives is presented. Currently, the variable-speed induction motor replaces the DC motor drive in a wide range of applications, including electric vehicles where quick dynamic response is required. This is now possible as a result of significant improvements in the dynamic performance of electrical drives brought about by technological advancements and development in the fields of power commutation devices, digital signal processing, and, more recently, intelligent control systems. The system’s reliability and robustness are improved, and the cost, size, and upkeep requirements of the induction motor drive are reduced through control strategies without a speed sensor. Successful uses of the induction motor without a sensor have been made for medium- and high-speed operations. However, low speed instability and instability under various charge perturbation conditions continue to be serious issues in this field of study and have not yet been effectively resolved. Some application such as traction drives and cranes are required to maintain the desired level of torque down to low speed levels with uncertain load torque disturbance conditions. Speed and torque control is more important particularly in motor-in-wheel traction drive train configuration where vehicle wheel rim is directly connected to the motor shaft to control the speed and torque. Novelty of the proposed work is to improve the dynamic performance of conventional controller used of model reference adaptive system speed observer using both type-1 and type-2 fuzzy logic controllers. Purpose. In proposed scheme, the performance of the engine is being controlled, fuzzy logic controller is controlling the estimate rotor speed, and results are then compared using type-1 and type-2. Method. For a two-wheeled motorized electric vehicle, a high-performance sensorless wheel motor drive based on both type-2 and type-1 fuzzy logic controllers of the model reference adaptive control system is developed. Results. Proved that, using fuzzy logic type-2 controller the sensorless speed control of the electrical differential of electric vehicle EV observer, much better results are achieved. Practical value. The main possibility of realizing reliable and efficient electric propulsion systems based on intelligent observers (type-2 fuzzy logic) is demonstrated. The research methodology has been designed to facilitate the future experimental implementation on a digital signal processor.

У цій роботі представлений новий підхід до оцінки швидкості колісних електромобілів із двома незалежними задніми приводами. В даний час асинхронний двигун із регульованою швидкістю замінює двигун постійного струму в широкому діапазоні застосувань, включаючи електромобілі, де потрібний швидкий динамічний відгук. Тепер це можливо внаслідок значного покращення динамічних характеристик електроприводів, викликаного технологічними досягненнями та розробками в галузі пристроїв комутації потужності, цифрової обробки сигналів та останнім часом інтелектуальних систем управління. Надійність та стійкість системи підвищуються, а вартість, розмір та вимоги до обслуговування асинхронного двигуна знижуються завдяки стратегіям керування без датчика швидкості. Успішне використання асинхронного двигуна без датчика було виконано для роботи на середніх та високих швидкостях. Проте низькошвидкісна нестабільність і нестабільність за умов збурення заряду продовжують залишатися серйозними проблемами у цій галузі досліджень і досі не вирішені ефективно. У деяких застосуваннях, таких як тягові приводи та крани, потрібно підтримувати бажаний рівень крутного моменту аж до низьких рівнів швидкості з невизначеними умовами збурення крутного моменту навантаження. Контроль швидкості і крутного моменту більш важливий, особливо в конфігурації тягової трансмісії з двигуном в колесі, де обід колеса транспортного засобу безпосередньо з'єднаний з валом двигуна для управління швидкістю і крутним моментом. Новизна запропонованої роботи полягає у поліпшенні динамічних характеристик звичайного регулятора, що використовується в еталонній моделі спостерігача швидкості адаптивної системи з використанням регуляторів нечіткої логіки як першого, так і другого типу. Мета. У запропонованій схемі контролюються характеристики двигуна, нечіткий логічний контролер управляє оцінною частотою обертання ротора, а потім порівнюються результати з використанням типу 1 і типу 2. Метод. Для двоколісного моторизованого електромобіля розроблено високопродуктивний бездатчиковий двигун-привід коліс на основі нечітких логічних контролерів як 2-го, так і 1-го типів еталонної системи адаптивного управління. Результати. Доведено, що з використанням регулятора нечіткої логіки 2-го типу для бездатчикового управління швидкістю EV-спостерігача електричного диференціала електромобіля досягаються значно кращі результати. Практична цінність. Показано принципову можливість реалізації надійних та ефективних електрореактивних рухових установок на основі інтелектуальних спостерігачів (нечітка логіка 2-го типу). Розроблено методологію дослідження для полегшення майбутньої експериментальної реалізації на цифровому сигнальному процесорі.
Keywords: electrical vehicle; induction machines; model reference adaptive system; field oriented control; electric differential; fuzzy logic controller; електромобіль; асинхронні машини; еталонна адаптивна система; полеорієнтоване керування; електричний диференціал; регулятор з нечіткою логікою